The Impact of Human Capital on Organizational Performance through the Mediating Role of Social Capital: A Field Study at the Mobile Phone Companies in Yemen - Murad Mohammed Al-Nashmi; Mohammed Ali Al-Ansi (University of Science and Technology, Sana’a, Yemen, 2023)
The study aimed at identifying the impact of social capital on organizational performance, in mobile phone companies in Yemen. A descriptive analytical method was adopted, and a questionnaire was designed for data collection. The study sample consisted of 327 male and female employees from all administrative selected levels. A number of inferential statistical methods were followed using the SPSS. The study mainly revealed a significant impact of human capital on organizational performance through social capital.